pengaruh partisipasi pendidikan terhadap persentase penduduk miskin di DKI Jakarta 2009-2013 - dini amaliah (Faktor Jurnal Ilmiah Kependidikan, 2015)
The aim of this study was to determine how much Influence of the Gross Enrolment Ratio (GER) and net enrollment ratio (NER) of the Percentage of Poor (Case Studies in Jakarta In the Year 2009-2013). The research method using a quantitative approach. Unit analyzed were the percentage of poor people (PPM), the gross enrollment rate (GER) and net enrollment ratio (NER). Source of data is secondary data in the form of books, dictionaries, scientific articles, data collected and published by the Central Bureau of Statistics (BPS). Hypothesis testing concluded that There was no significant effect of GER and enrollment at the percentage of poor people in Jakarta in 2009-2013 either partially or jointly represented by the magnitude of 0.572 calculated F <F table 9.55 on the level 0.05 significant.